(untitled) (Research, Society and Development, 2020)
The benthic macroinvertebrates are organisms of extremely importance to the energy flow of lotic ecosystems, acting as a link between basal resourcers and predators. This study aimed to analyze patterns of abundance, richness and diversity of a benthic macroinvertebrates community in different types of substrate and different velocities of water. The study was carried on in a stretch of 40 meters of a headwater stream located at the Tijuca National Park, the Tijuca River. The sampling was perfomed in September 2016. We sampled four types of samples, which we denominated as “habitats”: litter in riffle, litter in pool, sand in riffle and sand in pool. A total total of 2.208 individuals were collected, with most of them being immature insects. We confirmed our assumptions by finding difference between the composition of the four types of habitats. It was found higher abundance, richness and diversity in litter habitats, confirming that the characteristics of this type of substrate are more favorable for the majority of the benthic macrofauna.